Inhibition of Spermidine/Spermine N1‐Acetyltransferase Activity: A New Therapeutic Concept in Rheumatoid Arthritis. Issue 7 (July 2014) - Neidhart, Michel; Karouzakis, Emmanuel; Jüngel, Astrid; Gay, Renate E.; Gay, Steffen
<x xml:space="preserve">Abstract</x> Objective Changes in polyamine‐modulated factor 1 (PMF‐1) promoter methylation might favor the expression of spermidine/spermine N1‐acetyltransferase 1 (SSAT‐1), causing excessive consumption of S‐adenosyl methionine (SAM). This study was undertaken to evaluate the effect of SSAT‐1 activity inhibition, either alone or in combination with SAM. Methods Synovial fibroblasts were isolated from patients with rheumatoid arthritis (RA) or osteoarthritis (OA). PMF‐1 promoter methylation was determined by pyrosequencing. Small interfering RNAs (siRNAs) against SSAT‐1 were transfected weekly in RA synovial fibroblasts (RASFs). In addition, synovial fibroblasts were treated with diminazene aceturate (DA), an inhibitor of SSAT‐1. SSAT‐1, 5‐methylcytosine (5‐MeC), adenosyl methionine decarboxylase (AMD), PMF‐1, DNA methyltransferase 1 (DNMT‐1), CXCL12, β1 integrin, and CD44 levels were measured by flow cytometry. Putrescine levels were determined by colorimetry. Levels of matrix metalloproteinases were measured by enzyme‐linked immunosorbent assay. Cell adhesion was tested. The SCID mouse model of RA was used to monitor the invasiveness of RASFs. Results RASFs showed elevated SSAT‐1, AMD, and PMF‐1 levels. However, PMF‐1 promoter methylation was unchanged. Transfection of siRNA targeting SSAT‐1 increased 5‐MeC levels within 21 days. Similarly, DA increased 5‐MeC levels in RASFs. In addition, DA increased the levels of DNMT‐1, decreased the levels of AMD, putrescine, activation markers, and MMP‐1, and altered the adhesion of RASFs. DA was more efficient in RASFs with higher levels of SSAT‐1. Most interestingly, the combination of DA and SAM reduced the invasiveness of RASFs by 70%. Conclusion The use of DA alone or in combination with SAM/l‐methionine might introduce a new therapeutic concept in RA. This is the first therapy that would directly target RASFs and thereby inhibit ongoing joint destruction.